Modelling, control and frequency domain analysis of a tidal current conversion system with onshore converters. Issue 2 (1st February 2016) - Sousounis, Marios Charilaos; Shek, Jonathan K.H.; Mueller, Markus A.
Abstract : To optimise a tidal energy conversion system, the operation, maintenance and power generation aspects have to be taken into account. As a result the key focus of this study is to propose and investigate an alternative method of implementing a tidal energy conversion system using a pitch‐regulated turbine and a variable‐speed squirrel cage induction generator with long distance converters. The generator power output can be optimised by utilising variable‐speed control strategies allowing the system to operate at maximum power coefficient while availability can be increased by reducing the components installed offshore by using long three‐phase cables between the generator and onshore voltage source converters. The tidal current energy conversion system is investigated by developing a full resource‐to‐grid model in MATLAB/SIMULINK and by performing system analysis regarding the effects of harmonics in the long subsea cables. Simulation results show that optimised filter design and the choice of suitable operating frequency for the generator controller can minimise the overvoltages associated with the harmonics and the reflecting voltage waves in the cables.